Doing business in 2004 : Understanding Regulation - World Bank (Doing Business, 2003)
An important new annual publication from the World Bank, Doing Business in 2004 provides both qualitative and quantitative information on the business climate in over 130 countries. Doing Business constructs a new set of indicators on the regulatory environment for private sector development and provides a collection of informative case studies of real-life experiences. Doing Business in 2004 covers the fundamental aspects of a business life cycle, from starting a business to bankruptcy. Topics include access to credit, bankruptcy, entry regulations, contract enforcement, and labor regulations. Unique in its approach, Doing Business provides both the accurate data and in-depth analysis necessary to assess the environment for doing business, and offers answers to these critical questions: Which is the most expensive country for starting a new business? Which countries have the most rigid regulations on hiring and firing? Which countries have the most extensive business entry procedures? Why does heavy regulation lead to inefficiency and corruption? What countries are most efficient in the area of contract enforcement? How do clearly-defined property rights enhance prosperity? What are the most successful regulatory models? Why? Over the next two years, Doing Business will address additional topics, indicator sets will be updated and the collection of case-studies added to. Through its ambitious agenda, Doing Business will provide an understanding of business environments throughout the world, the factors that influence them, and how conducive they are to private sector development. Doing Business is a comprehensive resource for investors, economic advisers, business developers and policymakers